Examining the use of personal pronouns in political speeches by Tun Dr. Mahathir and Mr. Trump / Nur Ilyana Elisa Aiman Haris Fadzilah and Maizura Mohd Noor - Aiman Haris Fadzilah, Nur Ilyana Elisa; Mohd Noor, Maizura (Universiti Teknologi MARA, 2021)
Personal pronouns are often used to the point they often get overlooked. Unlike content words, they do not convey meaning but portray the perception of the speaker (Nakaggwe, 2012). Looking deeper into this, personal pronouns have the power to include or exclude a person or people of the subject (Khafaga, 2021), and it is crucial to master them especially in the political context. However, cultural differences exist in the use of personal pronouns since culture affects the way a person communicates and interprets information (Gocheco, 2012). For this reason, this qualitative research attempts to identify the use of personal pronouns, specifically those that demonstrate inclusiveness and exclusiveness, in the collectivistic Malaysian and individualistic American cultures, and compare the similarities and differences in the use of personal pronouns in speeches given by Tun Dr. Mahathir who represents the collectivistic Malaysian culture and Mr. Trump who represents the individualistic American culture. The AntConc software was used to determine the speech profiles and identify the personal pronouns based on the coding schemes and guidelines. It was found that the most popular personal pronoun used in their speeches is we, while the least popular are me and the subject singular you. They was used more frequently by Tun Dr. Mahathir to indirectly address the audience, while Mr. Trump opted to directly convey his message by using the plural you. The results have practical implications for speech writing and political persuasion and negotiation skills.